A case of chromophobe renal cell carcinoma in a 12-year-old girl - Okabe, Ko (Int Cancer Conf J, 2015)
Renal cell carcinoma (RCC) accounts for only 2–6 % of pediatric renal tumors. Chromophobe RCC is very rare in pediatric patients, with only a few cases reported. A 12-year-old girl who had abdominal and left flank pain visited the pediatric clinic of a local hospital. A uniformly enhanced tumor measuring 2.5 cm × 2.3 cm was found on computed tomography. On magnetic resonance imaging, T2-weighted images showed a solid tumor with hyperintensity suggesting intratumoral necrosis. We considered RCC and Wilms' tumor as differential diagnoses, but we could not reach a definitive diagnosis from the radiographic findings. We then performed right partial nephrectomy with regional lymph node dissection. The histopathological diagnosis was pT1aN0 chromophobe RCC. After the surgery, no recurrence has been observed for 15 months.